1979
DOI: 10.1002/mrc.1270121007
|View full text |Cite
|
Sign up to set email alerts
|

Etude en Résonance Magnétique Nucléaire du Carbone‐13 de N‐Aryl Pyrazolines‐2 Diversement Substituées. Effets de Substituant et Etude Conformationnelle

Abstract: The -C chemical shifts of 1-phenyl-2-pyrazoline and 25 N-nitropheny1-2-pyrazolines, with different substituents on the heterocyclic ring, have been assigned. These values are discussed as a function of the steric and electronic nature of the various substituents. The steric effects produced conformational modifications, both in the nitrophenyl and 2-pyrazoline moieties, which explain some of the chemical shifts.Les dkplacements chimiques du carbone-13 de la phknyl-1 pyrazoline-2 et de vingt-cinq N-nitrophhyl p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…5-methyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3c , mp: 179–180 °C), 3,5-dimethyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1-pyrazole ( 3d , mp: 174–176 °C), 3-isopropyl-4,4-dimethyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3h , mp: 201–202 °C), 3- tert -butyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3i , mp: 144–145 °C), 3-bromo-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3o , mp: 176–177 °C), , and 3-bromo-5-methyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3q , mp: 186–187 °C). , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5-methyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3c , mp: 179–180 °C), 3,5-dimethyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1-pyrazole ( 3d , mp: 174–176 °C), 3-isopropyl-4,4-dimethyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3h , mp: 201–202 °C), 3- tert -butyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3i , mp: 144–145 °C), 3-bromo-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3o , mp: 176–177 °C), , and 3-bromo-5-methyl-1-(2,4,6-trinitrophenyl)-4,5-dihydro-1 H -pyrazole ( 3q , mp: 186–187 °C). , …”
Section: Methodsmentioning
confidence: 99%
“…At the beginning, our own research , consisted of extending the reaction discovered by Mousseron et al to other pyrazolines and other halonitrobenzenes. Subsequently, when 1 H, 13 C, 15 N NMR was available, a series of papers were devoted to the use of these techniques to structural studies of nitrophenylpyrazolines. A less explored approach to the structure of 1-nitrophenyl-2-pyrazolines was the use of mass spectrometry to determine the gas-phase basicities of these compounds, whose p K a values we have previously determined.…”
Section: Introductionmentioning
confidence: 99%
“…Compound (12Ag) 3 was prepared according to reference Dias et al [ 34 ] Antipyrine 1 is a commercial compound. 1‐(2,4‐dinitrophenyl)‐3,5‐dimethyl‐4,5‐dihydro‐1 H ‐pyrazole 2 and tris(2‐methyl‐1 H ‐benzimidazolyl) methane were reported in references, [ 51,52 ] respectively. Compound 4 was synthesized by Ana San‐Félix's research group according to reference San‐Félix et al53 The origin of the compounds of Figure 4, except 5 and 6 that are commercial, were prepared for this work according to literature procedures: 7, 54 8 55 and 9.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of and spectroscopic data for all the 4,5-dihydropyrazoles used in this study (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) can be found in the literature. [12][13][14][15][16][17] Basicity measurements. The pK a values of the 16 dihydropyrazoles 5, 8-17, 6 and 18-21 in water at 20°C are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%